Off-Label Prescription of Psychopharmacological Drugs in Child and Adolescent Psychiatry. Issue 5 (October 2016) - Braüner, Julie Vestergaard; Johansen, Lily Manzello; Roesbjerg, Troels; Pagsberg, Anne Katrine
Abstract : Abstract: This study aimed to describe the frequency of off-label prescriptions of psychopharmacological drugs in a child and adolescent psychiatric setting. A cross-sectional study was conducted on November 1, 2014, including all inpatients and outpatients at the Mental Health Centre for Child and Adolescent Psychiatry, Capital Region of Denmark, aged 0 to 17 years receiving medical treatment with antidepressants, antipsychotic agents, benzodiazepines, melatonin and/or attention deficit hyperactivity disorder (ADHD) medication. We included a total of 5555 prescriptions representing 2932 patients. The main findings were that 32.3% of all prescriptions were off-label, and 41.6% of subjects received at least 1 off-label prescription. The most frequent off-label category was low age, 72.2%, meaning that the drug was not approved for the age group of the patient. The off-label rates for each drug class were as follows: melatonin, 100%; antipsychotic agents, 95.6%; benzodiazepines, 72.5%; antidepressants, 51.1%; and ADHD medication, 2.7%. Prescription of 2 or more psychopharmacological drugs per patient was common (31.5%). The group of subjects with 4 or more prescriptions (n = 36) was characterized by a higher frequency of inpatients, older age, and a different distribution of diagnoses. This study found a frequent use of off-label prescriptions when treating children and adolescents with psychopharmacological drugs other than ADHD medication. In addition, prescription of more than 1 psychotropic drug is common. These findings support the need for extending the evidence base for psychopharmacologic treatment in children and adolescents. Abstract : Supplemental digital content is available in the text.